THE COMPARATIVE ANALYSIS OF MORTGAGE REFINANCING MODELS - Moskvichova , O.S. (The actual problems of regional economy development, 2020)
In a difficult financial, economic and political situation, the failure of the credit system can certainly cause a banking crisis, which has repeatedly happened in the history of Ukraine. Problems with liquidity and solvency of bank credit institutions in this situation can be solved by the NBU as a lender of last resort, which provides support to banks through refinancing. However, the crisis in the domestic banking system encourages a new consideration of bank refinancing, which encourages the search for its effective tools and mechanisms, including mortgage refinancing. The experience of financial crises has shown that mortgage refinancing models need further careful study, as they are primarily related to the risks inherent in a particular model. The purpose of the article is a comparative analysis of different models of mortgage refinancing, assessment of their inherent risks and study of the distribution of these risks between the participants of mortgage lending and refinancing. The methodological basis of the study are general and special methods of cognition, research literature, scientific works of domestic scientists on refinancing, mortgage refinancing, especially in times of crisis, as well as other methods such as systems analysis; synthesis, statistical method and others. In world practice, there are three main models of mortgage refinancing, each of which, along with common features for all models, has specific, unique features. The oldest and probably the most reliable is the so-called single-level model, common in European and many other countries. Two-tier models, common in the United States and some Asian countries, and, to some extent, in France, are more mobile than the first, but also more risky. The study of the risks associated with the operation of a particular model is very relevant and therefore deserves considerable attention from scientists and practitioners. The scientific novelty lies in the comparative analysis of mortgage refinancing models and their relationship with financial crises. It is proposed to create a mortgage mechanism that combines the parallel coexistence of two models (one- and two-level) functioning of the mortgage lending market. The practical significance of the article lies in the solved dilemmas: how to effectively and safely for all participants in the credit market to use the opportunities provided by refinancing models in the financial and economic crisis.